Toward the synthesis, fluorination and application of N–graphyne. Issue 66 (3rd November 2020) - Abdi, Gisya; Filip, Anna; Krajewski, Michał; Kazimierczuk, Krzysztof; Strawski, Marcin; Szarek, Paweł; Hamankiewicz, Bartosz; Mazej, Zoran; Cichowicz, Grzegorz; Leszczyński, Piotr J.; Fijałkowski, Karol J.; Szczurek, Andrzej
Abstract : The appearance of PTFE-like nanochains in the structure of fluorinated N–graphyne strongly influences both electrochemical and biological properties. Abstract : The discovery of properties and applications of unknown materials is one of the hottest research areas in materials science. In this work, we navigate a route towards these goals by the development of a new type of graphyne nanostructure. It is synthesised by a Sonogashira cross-coupling reaction of 1, 3, 5-triethynylbenzene with cyanuric chloride resulting in an extended carbon-based material called TCC. Also, we modify the obtained TCC via fluorination using XeF2 at various concentrations to investigate the effect of fluorination on the triple bonds and the conjugated structure of graphyne. In this study, we put special emphasis on the determination of the impact of the fluorine content and the type of CF functionalities on the morphology, chemical and electronic structure, biocompatibility, electrical conductivity and possible applicability as anode materials for Li-ion batteries. The obtained results indicate that the character of C–F bonds influences the final properties of fluorinated materials. The polar C–F bonds are preferable for cell proliferation while CF2 groups are most suitable for battery devices, however, the appearance of PTFE-like units may have a negative impact on battery specific capacitance as well as on cell viability.